The in vitro solubility of calcium: One great importance for the breeding of birds? - Buendía Molina, Marilyn Aurora (2020)
The objective of the present study was to evaluate in vitro the solubilization of two sources of calcium (calcium carbonate and conchilla), with two particle sizes (180 μ and 4 mm), by the weight loss technique and its importance in the feeding of the birds. For it, completely randomized design was used with four treatments (T1, Calcium Carbonate Flour; T2, Granulated Calcium Carbonate; T3, Conchilla Flour; T4, Granulated Conchilla) and three repetitions. T2 and T4 showed lower solubility than treatments T1 and T3 (p ›0.05). The calcium carbonate flour showed the highest solubility. The difference in solubility between calcium sources with the same grain size can be due to the mineral composition and its physical characteristics. The selection of the source of calcium (Ca) is of great importance for poultry farming and follows economic criteria.